2010
DOI: 10.4025/actascianimsci.v32i4.7829
|View full text |Cite
|
Sign up to set email alerts
|

Urea levels in multiple supplement for lambs grazing on buffelgrass

Abstract: ABSTRACT. The objective of present trial was to evaluate the intake of supplement dry matter, productive performance, carcass traits, and weight and yields of commercial meat cuts of lambs grazing on dormant buffelgrass pastures and receiving multiple supplementation containing different urea levels. Urea levels used were: 5, 8, 11 and 14% on dry matter. Thirty-six male lambs were used, nine animals per treatment, with 18.0 ± 2.0 kg initial body weight, distributed into four groups. The experimental design was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Voltolini et al (2009a) evaluated the carcass traits of Santa Ines lambs grazing Tifton 85 grass non supplemented or not with 0.20 kg/day and they observed 41.94% of hot carcass weight to non supplemented animals and 43.30% to 44.64% for supplemented animals, in the same region. In addition, Voltolini et al (2009b) found values of 43.89 to 44.50 kg for the hot carcass weight to lambs grazing Buffel grass receiving concentrate supplementation in the dry period in Brazilian Northeast semiarid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Voltolini et al (2009a) evaluated the carcass traits of Santa Ines lambs grazing Tifton 85 grass non supplemented or not with 0.20 kg/day and they observed 41.94% of hot carcass weight to non supplemented animals and 43.30% to 44.64% for supplemented animals, in the same region. In addition, Voltolini et al (2009b) found values of 43.89 to 44.50 kg for the hot carcass weight to lambs grazing Buffel grass receiving concentrate supplementation in the dry period in Brazilian Northeast semiarid.…”
Section: Resultsmentioning
confidence: 99%
“…However, the production system in this region is characterized as extensive or ultra-extensive, showing low stocking rate of native pastures, low meat and milk yield, low reproductive efficiency of animals and high mortality rate of herds, resulting in a low economic performance to farmers (MOREIRA et al, 2008;VOLTOLINI et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Voltolini et al (2010) evaluated the productive performance of Brazilian Northeast semi-arid native lambs and reported an average daily gain variation of 0.025 to 0.047 kg animal -1 day -1 in the dry period in the same region. These results are similar to the observed in the present trial and indicate a possibility to obtain low to moderate average daily gain in the dry or rainy dry period of year, promoting an opportunity to produce, to avoid weight loss or death of animals.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, it enters senescence and rapidly loses its nutritional value. Voltolini et al (2010), evaluating performance of sheep grazing deferred buffelgrass supplied with urea, verified no more than 47 g daily gain and stated this low performance is due to difficulty of grazing deferred buffelgrass because pasture had high stem:leaf ratio. Thus, the cut, processing, and use in feedlot could improve animal performance.…”
Section: Introductionmentioning
confidence: 99%